Gabapentin for Acute Postoperative Pain Control in Total Abdominal Hysterectomy: A randomized controlled trial - Hathaipat Sukjariangporn; Sittichoke Mahasukontachat (The Royal Thai College of Obstetricians and Gynaecologists, 2021)
Objectives: To evaluate the effect of gabapentin 300 mg in relieving acute postoperative pain in patients undergoing total abdominal hysterectomy at Chonburi Hospital. Materials and Methods: A double-blind, randomized, controlled trial was performed on women scheduled for total abdominal hysterectomy at Chonburi Hospital from January 7, 2019 to April 26, 2019. All eligible participants were randomized by computer-generated with block of four into two groups to receive either 300 mg of gabapentin or placebo, orally two hours preoperative. Primary outcome was an additional opioid consumption. Secondary outcomes were time to first additional opioid requirement, pain score, sedative score, opioid-related adverse effects such as nausea/vomiting and pruritus, and gabapentin-related adverse effect as dizziness at 1, 2, 6, 10, 14, 18, 24 hours after surgery.Results: The results were analyzed from 60 participants (gabapentin N=30, placebo N=30). Mean of total opioid consumption was lower in the gabapentin group compared with the placebo group (14.23 ± 9.78 mg vs 21.77 ± 12.71 mg, p = 0.012), especially during the first 4 hours. Time to first additional opioid requirement was longer in the gabapentin group. The average visual analogue scale and nausea/vomiting scores were lower in the gabapentin group. There was no difference between the means of pruritus and sedative scores. However, dizziness score was found to be higher in the gabapentin group in the first 6 hours.Conclusion: Premedication with 300 mg of gabapentin orally 2 hours prior to elective total abdominal hysterectomy for patients with both benign and malignant conditions was effective for postoperative pain control with few adverse effects occurred.